The Haar state on the Vaksman-Soibelman quantum spheres - Mikkelsen, Max Holst; Kaad, Jens (MATHEMATICA SCANDINAVICA, 2023)
In this note we present explicit formulae for the Haar state on the Vaksman-Soibelman quantum spheres. Our formulae correct various statements appearing in the literature and our proof is straightforward relying simply on properties of the modular automorphism group for the Haar state.